Paediatric dermatology - Lewis-Jones, Sue; Murphy, Ruth (Dermatologist) (Oxford : Oxford University Press, 2020)
Fully revised and updated, this second edition is full of practical advice, clinical photographs, useful algorithms, and management plans, making'Paediatric Dermatology' an accessible, indispensable guide for all healthcare professionals faced with the assessment, diagnosis, and treatment of children with skin diseases.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 20, 2020).
Keywords: Pediatric dermatology -- Handbooks, manuals, etc